Assessment of environmental and resource-saving technologies and technical means for processing and disposal of man-made formations and waste - Lyashenko, Vasil; Khomenko, Oleh; Chekushina, Tatjna; Topolnij, Fedor; Dudar, Tamara (Technology audit and production reserves, 2020)
The object of research is environmental and resource-saving technologies and technical means for the processing and disposal of man-made formations and waste in the underground mining of mineral deposits with backfilling of the worked-out space. One of the most problematic areas is the management of the state of ore-containing energy-disturbed massifs and the delivery of hardening filling mixtures to the place of their laying, as well as the shortage of components for their preparation. This increases the importance of the management of the stress-strain state (SSS) of the rock mass, ensuring the safety of the earth’s surface from destruction and vital activity of the population living in the zone of influence of the mining region. The paper presents the main scientific and practical results of the substantiation of technologies and technical means for the disposal of mining and metallurgical waste into underground goaf (man-made voids) as components of hardening filling mixtures of various composition and strength. Methods of theoretical generalizations with the use of mathematical statistics, physical and mathematical modeling, with the implementation of calculations and feasibility studies, laboratory and field experimental studies, industrial tests in the conditions of operating enterprises of mining and metallurgical production are described. On the basis of the study of the mechanism of stress-strain state of a rock mass using geophysical and surveying methods, an environmental technology for extinguishing technogenic voids in energy-disturbed massifs is proposed. This technology makes it possible to ensure the safety of the earth’s surface and the vital activity of the population living in the zone of influence of mountain objects (mines, dumps, industrial sites for stowing complexes, tailings, ore-processing plants (OPP), etc.). It was found that for the mines of the state enterprise «VostGOK» (Ukraine), the utilization rate of own production waste for hardening backfill is from 0.45 to 0.68; hydraulic – from 0.56 to 0.75; free-flowing – 0.62, and the extraction of each ton of commercial ore is accompanied by the output of 0.7-0.8 tons of waste. An assessment of the utilization level of wastes of mining and metallurgical production is given and an inventory for wastes of mining enterprises is given, which gives an estimate and directions of their possible use for the needs of the national economy. The research results can be used in underground mining of complex ore deposits and mining and metallurgical production.